Acculturation Strategies of Indigenous Students in Learning English: A Qualitative Inquiry - Jiki Clarice Dedel; Gywneth Jane Harani; Freizel Ann Plaza; Christian Jay O. Syting (CV. Tripe Konsultan, 2023)
This qualitative descriptive study aimed to identify the factors that contribute to social and psychological distance of indigenous English learners, their strategies to reduce these factors, and their insights about acculturation. To this end, ten indigenous English major students at the University of Mindanao were interviewed. Through thematic analysis, findings revealed that the factors involved in the social distance of the participants were incongruence and dissimilarity between 2LL and TL group, negative attitudinal orientation towards the TL group, and cohesiveness of the 2LL group, while the psychological factors were language shock, high affective filter, and ego permeability. To address these factors, the participants implemented the following strategies: positive intergroup relationship, accommodation of the TL, perceptual distortions in favor of outgroup vitality, cultivation of positive self-image, and development of TL skills. In terms of the insights of the participants, this study observed empowerment of indigenous community, enhancement of exposure to second language input, instructional scaffolding in L2 teaching, implementation of intercultural approach, immersion to the outgroup, and alleviation of affective filter. The results evinced how the acculturation dilemmas faced by indigenous English learners prevented effective second language acquisition. From this, appropriate solutions may be formulated to ensure successful acculturation in the classroom.